2021
DOI: 10.1002/ps.6598
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Nilaparvata lugens (Hemiptera: Delphacidae) to triflumezopyrim: inheritance and fitness costs

Abstract: BACKGROUND: Triflumezopyrim, a novel commercialized mesoionic chemical insecticide, has been confirmed as a promising insecticide for efficiently controlling the brown planthopper, Nilaparvata lugens (Stål). Here, a laboratory triflumezopyrimresistant (TR) strain and an isogenic susceptible (TS) strain were established to characterize the inheritance and fitness costs of triflumezopyrim resistance in N. lugens.RESULTS: After 29 generations of successive selection with triflumezopyrim, the TR strain developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In our study, the Tri-sel strain was used to determine that triflumezopyrim resistance is inherited as a polygenic, autosomal and incompletely dominant trait. Qin et al 35 found that after 29 generations of successive selection with triflumezopyrim, N. lugens (Hemiptera: Delphacidae) developed 155.23-fold resistance and triflumezopyrim resistance was inherited as an autosomal, polygenic and codominant trait. In this population, the values of the degree of dominance (D) for F 1 RS and F 1 SR were −0.05 and 0.06, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the Tri-sel strain was used to determine that triflumezopyrim resistance is inherited as a polygenic, autosomal and incompletely dominant trait. Qin et al 35 found that after 29 generations of successive selection with triflumezopyrim, N. lugens (Hemiptera: Delphacidae) developed 155.23-fold resistance and triflumezopyrim resistance was inherited as an autosomal, polygenic and codominant trait. In this population, the values of the degree of dominance (D) for F 1 RS and F 1 SR were −0.05 and 0.06, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…17 It has been reported that there is a fitness cost after the resistance of N. lugens to various insecticides, such as imidacloprid, nitenpyram, sulfoxaflor and triflumezopyrim, and life parameters such as survival rate, fecundity, hatchability, emergence rate, copulation rate of the resistant population were significantly reduced. 26,41,45,46 Our fitness cost study showed the Pym-R 90 and WA2020 strain had obvious disadvantages in their developmental duration, emergence rate and hatchability. It is worth noting that the reduced hatchability of N. lugens resistant to pymetrozine is the main factor contributing to their low fitness.…”
Section: Discussionmentioning
confidence: 87%
“…However, there is also the phenomenon that the fitness of insects increases after they become resistant to a certain insecticide, 44 which is the result of various factors such as the type of insect, insecticide and the environment 17 . It has been reported that there is a fitness cost after the resistance of N. lugens to various insecticides, such as imidacloprid, nitenpyram, sulfoxaflor and triflumezopyrim, and life parameters such as survival rate, fecundity, hatchability, emergence rate, copulation rate of the resistant population were significantly reduced 26, 41, 45, 46 . Our fitness cost study showed the Pym‐R 90 and WA2020 strain had obvious disadvantages in their developmental duration, emergence rate and hatchability.…”
Section: Discussionmentioning
confidence: 99%
“…The life-table data for the N. lugens individuals were analyzed using an age-stage, two-sex life-table theory ( Qin et al, 2021 ). Through calculations, the adult pre-oviposition period (APOP), total pre-oviposition period (TPOP), population parameters, and other life-table parameters were obtained.…”
Section: Methodsmentioning
confidence: 99%